Yogya Kota Sumber Department Store’s Digital Communication Strategy for Building Customer Interest on Instagram - Muhammad Faizal Zakky; Khaerudin Imawan (Jurnal Impresi Indonesia, 2026)
Advances in communication technology and social media have made it necessary for retail companies to implement effective communication strategies to build customer interest. One of the most widely used platforms today is Instagram because of its interactive visual nature. This study aims to identify and analyze Yogya Kota Sumber’s digital communication strategies on Instagram and assess the extent of their success in building customer interest. This study employed a descriptive qualitative methodology, using data collection techniques such as observing the Instagram account @yogyakotasumber, conducting interviews with the account manager, and reviewing supporting documentation. Integrated Marketing Communication theory was applied to analyze the data, particularly in relation to promotional communication, direct marketing, and interactive marketing. AIDA theory was also applied to assess the effectiveness of this strategy. The results indicate that Yogya Kota Sumber utilized Instagram features in an integrated manner through promotional content, activities, regular discount programs, two-way communication with customers, CSR activities, limited direct marketing, interactive features, and collaborations with influencers. This strategy successfully captured public attention, sparked curiosity, triggered interest, and ultimately encouraged customers to take concrete action. Thus, Yogya Kota Sumber’s Instagram-based digital communication strategy is considered an effective way to build long-term customer interest.